Sosialisasi Penerapan Instrumen Tes Kebugaran Siswa Indonesia (TKSI) pada Mahasiswa PGSD: Penelitian - Naheria; Gyta Krisdiana Cahyaningrum; Didik Cahyono; Muhammad Sukron Fauzi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This activity aims to provide conceptual understanding, as well as practical skills to students of the Elementary School Teacher Education Study Program (PGSD) in implementing the Indonesian Student Fitness Test (TKSI) Phase C instrument, by using socialization and simulation methods through lecture, discussion and demonstration approaches that aim to provide knowledge and skills that can be directly applied by students, The evaluation results obtained that 80% of students showed very good abilities and 20% showed good abilities in explaining the benefits of implementing fitness tests using the TKSI instrument to students and teachers, and 85% of students were very skilled and 15% were skilled in implementing physical fitness tests using the TKSI instrument, this is supported by the results of direct observations in the field which showed that students were able to carry out all stages of the test activities systematically, starting from preparing the equipment, arranging the place, explaining the procedures, to technical demonstrations of each test item, so it can be concluded that overall, this socialization activity succeeded in providing theoretical and practical skills to PGSD students needed to measure and facilitate the optimal improvement of physical fitness of elementary school students.